Hypertrophic cardiomyopathy associated with sleep apnea: serious implications and cogent management strategy. (March 2015) - Aggarwal, Saurabh; Jan, M Fuad; Agarwal, Anushree; Tajik, A Jamil
<x xml:space="preserve">Abstract</x> Obstructive sleep apnea (OSA) affects an estimated 20 million adult Americans and is present in a large proportion of patients with hypertension and in those with other cardiovascular disorders, including hypertrophic cardiomyopathy (HCM). This review seeks to highlight concepts and evidence important to understanding the interactions between OSA and HCM, with particular attention to more recent advances in patient-oriented research. Studies of patients with HCM have found the prevalence of sleep-disordered breathing to range from 40 to 80%. Increased sympathetic activity, impaired vagal activity, increased afterload, insulin resistance and endothelial dysfunction have been proposed as potential mechanisms for the association. Specific questions include whether OSA is important in unmasking symptoms in hitherto undiagnosed patients with HCM, whether OSA in patients with established HCM accelerates disease progression and whether treatment of OSA results in clinical improvement, fewer cardiovascular events and reduced mortality. Because obesity, cardiovascular disease, metabolic syndrome, and diabetes are often present in patients with OSA, it can be difficult to attribute abnormalities evident in the sleep apnea patient with HCM to the effects of OSA, the effects of HCM or synergies between these conditions. Although further research is needed to answer these specific questions, recent investigations have clearly shown the coexistence of OSA and HCM, as well as elucidated the contribution of heightened sympathetic nerve activity in OSA to drug-refractory symptoms and worsening left ventricular outflow tract obstruction. This review aims to highlight the current literature available on the association of OSA and HCM, provide directions for future research and summarize the key features related to this association based on the authors' best understanding and experience.